Ocular Morbidity in the Correction of Orbital Hypertelorism and Dystopia: A 15-Year Experience. Issue 4 (April 2017) - Glass, Graeme E.; Hon, Kate A. V.; Schweibert, Kemmy; Bowman, Richard; Jones, Barry M.; Dunaway, David J.; Britto, Jonathan A.
Abstract : Background: Complex surgery for appearance change is controversial. Correction of orbital hypertelorism risks diplopia and loss of stereopsis for aesthetic gain. The risk-to-benefit ratio remains ill-defined. The aim of this study was to define specific ocular morbidity following orbital translocation. Methods: The authors compared stable preoperative and postoperative orthoptic indices (i.e., angle of strabismus, ocular motility, and acuity) for 23 consecutive patients who underwent orbital translocation between 2000 and 2015 and noted the requirement for corrective surgery. Results: Eighteen patients underwent 33 box osteotomies (15 bilateral and three unilateral). Five patients underwent facial bipartition. Diagnosis was craniofrontonasal dysplasia in 11, frontonasal dysplasia in six, facial cleft in four, and Saethre-Chotzen syndrome in two cases. Median grade of orbital hypertelorism was III. Median age at surgery was 13 years (range, 5 to 17 years). Nontransient change (favorable or unfavorable) in angle of strabismus was noted in 14 patients. Ocular motility was altered in 12. Six patients had stereopsis preoperatively that was disrupted in two cases because of changes in ocular alignment and/or motility. There was one perioperative ophthalmic emergency (superior orbital fissure syndrome) and three acute reexplorations for external ocular muscle entrapment. Corrective surgery for strabismus was performed for four patients. Three required secondary canthopexy and three required surgery for blepharoptosis. Conclusions: Orbital translocation is associated with ocular risks including changes to angle of strabismus, ocular motility, and (when present) loss of stereopsis. Secondary surgery to correct strabismus or eyelid malposition is common. Orbital translocation is an operative process, not a single procedure. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.